Enlaces e desenlaces : família escrava e reprodução endógena no Espírito Santo (1790-1871) - Ribeiro, Geisa Lourenço (2012)
The existence of slave families, for a long time hidden by the Brazilian historiography, is no longer questioned by researchers who currently focus on investigating its social, political and economical meanings. The spatial and chronological extent in which slavery developed in Brazil justifies the sustained interest in the subject, on which this paper refers to. The state of Espírito Santo, by its close relation with slavery and by sheltering in its territory food producing areas both in small farms and also in large farms devoted to agricultural exports, constituted a privileged locus for the analysis. From post-mortem inventories, ecclesiastical marriage records, reports made by the province presidents and also census, produced between the final decades of the colonial period and the Rio Branco Law, responsible for freeing the newborn children of slaves, in 1871, the analysis of the importance of endogenous reproduction has been sought, in other words, from the slave family to the reproduction of the slavocratic society. The main objective was pursued bearing in mind the initiative of individuals kept under bondages and set of interests that involved the familiar couplings and dissolutions.